Absceso Cerebral Debido a Embolización Sistémica - Catarina Cabral; Inês Santos; Joana Tavares; Joana Vaz (Galicia Clínica)
A brain abscess is a focal infection of the brain. It can be caused by hematogenous or direct spread, presenting with non-specific symptoms that can delay diagnosis. They are most often bacterial, but they can also be fungal, parasitic or granulomatous. Neurological manifestations such as stroke, meningitis, or brain abscess can develop from endocarditis, so this entity should always be considered and investigated. The authors present a case of a patient with a heart valve prosthesis for aortic stenosis and a brain abscess due to systemic embolization from subacute endocarditis.